Unique Characteristics of Youth Socialization (The Peerian Journal, 2025)
The article analyzes the characteristics of youth socialization, its role, and significance in society. The scientific approaches of scholars such as Giddings, Mead, and Parsons to the study of the socialization process are examined. It is also emphasized that socialization is the fundamental process of personality formation. The connections of youth socialization with cultural and social environments, as well as its interactions with various social institutions, are extensively covered